Collaborative Governance dalam Upaya Reintegrasi Sosial terhadap Anak yang Berkonflik dengan Hukum di Kota Yogyakarta - Hakam Biqy, Muhammad; Suyatno, Suyatno (Jurnal Ilmiah Administrasi Publik, 2025)
This research focuses on the governance of collaboration between government, private sector and civil society. In the process of social reintegration of children in conflict with the law (ABH) in Yogyakarta City. ABH have 3 (three) classifications, namely perpetrators, victims, and witnesses and all three are handled by different institutions. The research method used is descriptive qualitative. The research instruments were secondary data collection, interviews and focus group discussions. Secondary data collection is in the form of data processing of tasks and functions of stakeholders, Yogyakarta Decree No. 446 of 2022, and KPAID 2022 Year-End Report. In-depth interviews were conducted with DP3AP2KB, KPAID, and other institutions. While the data collection technique in the form of Focus Group Discussion was conducted at the SPPA Forum of Yogyakarta City. The purpose of this research is to describe the process of social reintegration and the collaborative governance process for ABH in Yogyakarta City. Broadly speaking, the collaboration dynamics of each stakeholder have been systematized, but the collaboration process still focuses on ABH perpetrators, while ABH victims and witnesses do not yet have a structured handling scheme.